Evaluation of Travel Medicine Status in Government Primary Health Care Centers in Riyadh Saudi Arabia: A Mixed-methods Study - Alsiyabi, Balqees Mohamed (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction and Objective: Travel medicine (TM) is a rapidly developing, very dynamic, and multidisciplinary field that calls for knowledge of numerous illnesses that can occur while traveling. Therefore, this study aimed to evaluate the TM status in Government Primary Health Care (PHC) Centers in Riyadh city Saudi Arabia. Materials and Methods: A cross-sectional observational study was conducted in August 2022 in Government PHC Centers in Riyadh city Saudi Arabia using multistage stratified random sampling. A total of 25 Health centers were drawn from the different regions of Riyadh, northern, south, west, east, and middle areas. The data used are primary data, obtained from physicians assigned in TM clinics using quantitative as well as qualitative data collection methods. Results: This study involved 30 physicians, 23 of whom are general practitioners and 7 of whom work in TM clinics. Sixteen (53.3%) of the participants were males and Saudis. The mean age was 41 years and the standard deviation was 11 years. About 46.7% of the participants are registrars or senior registrars. TM -related information is most commonly found in review articles and journals (26%), followed by websites and the internet (21%). Conclusion: There were missing communication links between TM clinics and PHC providers in the evaluation of TM clinics in PHC, which needed meetings and continuous training. The TM clinic also needed to develop a plan to raise public awareness about its services among doctors and the community.